Formulation of nanoemulsion: a comparison between phase inversion composition method and high-pressure homogenization method. (June 2015) - Kotta, Sabna; Khan, Abdul Wadood; Ansari, S. H.; Sharma, R. K.; Ali, Javed
Abstract: There is lot of confusion in the literatures regarding the method of production of nanoemulsion. According to some authors, only the methods using high energy like high-pressure microfluidizer or high-frequency ultra-sonic devices can produce actual nanoemulsions. In contrast to this concept, one research group reported for the first time the preparation of nanoemulsion by a low-energy method. Later on many authors reported about the low-energy emulsification method. The purpose of this work is to formulate, evaluate and compare nanoemulsions prepared using high-energy as well as low-energy method. Nanoemulsions formulated were based on the phase inversion composition technique (low energy method) and were selected from the ternary phase diagram based on the criterion of their being a minimum concentration of S mix used in the formulation. For high-pressure homogenization method (high energy method) Design-Expert software was used, and the desirability function was probed to acquire an optimized formulation. No significant difference ( p > 0.05) was observed in the globule size of formulations made by each method, but the value of poly-dispersibility index between the two methods was found to be extremely significant ( p < 0.001). A very significant difference ( p < 0.001) was observed in the drug release from formulations made by each method. More than 60% of the drug was released from all the formulations in the initial 2 h of the dissolution study.